The effect of rTMS intervention with different targets on neural remodeling in stroke patients: a randomized controlled trial - Li Zhao; Li Chen; Qiu Wang; Xinyi Li; Sha Li; Chunxiao Wan (Frontiers in Neurology)
BackgroundrTMS is widely used to improve motor function in patients with ischemic stroke, but there are few studies on different targets. In order to develop a clinical precision rehabilitation program, this study aims to explore the effects of rTMS at different targets on neural remodeling in patients with subcortical stroke by combining motor function assessment, multimodal MRI and electrophysiological methods.Methods69 stroke patients were randomly assigned to the sham group, M1 group, and SMA group. Functional assessment was performed using the exercise and balance scale, and rsfMRI, DTI, VBM, and MEP were used to evaluate the changes in rsFC, white matter tracts, gray matter volume, and neurophysiology before and after intervention.ResultsFollowing the intervention, the SMA group demonstrated significantly greater improvement in motor function compared to the M1 group (p < 0.05). Functional connectivity analysis revealed significantly increased resting-state functional connectivity (rsFC) in the contralateral dentate nucleus and ventromedial premotor area of the affected side in the SMA group relative to the M1 group (p = 0.0319), with this enhancement showing a strong positive correlation with balance function improvement (r = 0.637, p = 0.001). Structural MRI analysis indicated that while the M1 group exhibited a significant increase in gray matter volume (GMV) in the medial segment of the postcentral gyrus (p = 0.02), the SMA group showed significant GMV increases in the posterior cerebellum and chorionic lobule (p = 0.0428) that demonstrated a moderate positive correlation with improved balance function (r = 0.436, p = 0.038). Diffusion tensor imaging results showed significant differences in both fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values of the corticospinal tract between the M1 group and the other two groups, with both the M1 and SMA groups exhibiting significant changes in latency and amplitude measures compared to the sham group post-intervention.ConclusionHigh-frequency SMA-TMS intervention on the affected side has a better improvement than traditional M1 target in stroke with motor function. We provide neuroimaging and neurophysiological evidence for different target rTMS interventions in motor related networks after stroke.Clinical trial registrationwww.chictr.org.cn, identifier ChiCTR2200060955.